2006
DOI: 10.1007/s00148-006-0093-8
|View full text |Cite
|
Sign up to set email alerts
|

Oppositional identities and the labor market

Abstract: We develop a model in which non-white individuals are defined with respect to their social environment (family, friends, neighbors) and their attachments to their culture of origin (religion, language), and in which jobs are mainly found through social networks. We find that, depending on how strong peer pressures are, nonwhites choose to adopt "oppositional" identities since some individuals may identify with the dominant culture and others may reject that culture, even if it implies adverse labor market outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 37 publications
0
102
0
Order By: Relevance
“…We have seen that if the planner only subsidizes effort, then the optimal subsidy is given by (12), that is…”
Section: Effort Versus Assimilation Subsidymentioning
confidence: 99%
See 1 more Smart Citation
“…We have seen that if the planner only subsidizes effort, then the optimal subsidy is given by (12), that is…”
Section: Effort Versus Assimilation Subsidymentioning
confidence: 99%
“…In recent years, a number of empirical studies have shown that individuals or organizations who bridge 'structural holes' in networks gain significant payoff advantages. 12 7 Network formation and assimilation choices …”
Section: Finally Ifmentioning
confidence: 99%
“…4 In economics, different aspects of conformism and social norms have been explored from a theoretical point of view. To name a few, (i) peer pressures and partnerships (Kandel and Lazear 1992) where peer pressure arises when individuals deviate from a well-established group norm, e.g., individuals are penalized for working less than the group norm, (ii) religion (Iannaccone 1992, Berman 2000) since praying is much more satisfying the more average participants there are, (iii) social status and social distance (Akerlof 1980, Bernheim 1994, Battu et al, 2007, among others) where deviations from the social norm (average action) imply a loss of reputation and status. 5 To be more precise, the Bonacich centrality measure takes into account both direct and indirect friends of each individual but puts less weight to distant friends.…”
Section: Introductionmentioning
confidence: 99%
“…With probability 1 − α, she (incorrectly) believes that the worker is good. 10 A good worker is never mistaken for a bad one. Our results are robust to the case of a more general screening technology, which allows for the mistaken classification of good workers as long as the probability of making a mistake about bad workers is larger than the probability of making a mistake about good ones.…”
Section: Endogenous Evaluationsmentioning
confidence: 99%